PARADIGMA BARU SUPERVISI COACHING MODEL TIRTA SEBAGAI MANIFESTASI PENINGKATAN MUTU SEKOLAH - Jaka Nurhidayat; Wida Widaningsih; Sofyan Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to reach conclusions about coaching for supervision using the TIRTA flow and its effectiveness. The main focus in this research is related to the use of the TIRTA flow and its effectiveness in improving the quality of education. The research method used is using qualitative research with a literature review by looking for theoretical references that are relevant to the case or problem found. The results showed that Supervision Coaching Using Tirta Flow changed the perceptions of teachers and principals regarding the purpose of academic supervision. brings a positive impact on improving teacher performance and learning in the educational environment. In addition, the effectiveness of supervision using Tirta flow teachers get the opportunity to develop skills and potential, thus participating in improving the quality of learning. Using the TIRTA Model helps a teacher set and achieve professional goals and can improve teachers' reflective skills. Coaching supervision using the TIRTA model can also build a more collaborative working relationship between principals and teachers. the application of coaching using Alur Tirta can significantly improve teacher performance. This shows that the coaching technique using Alur Tirta is very effective in improving teacher performance.